Implementation of Mutammimah Book Learning on the Ability to Read the Kutub al-Turats in Madrasah Riyadlotusy Syubban Ponorogo: This study discusses the implementation of learning the mutammimah book on the ability to read the kutub al-turats at Madrasah Riyadlotusy Syubban Ponorogo. - Roni Susanto (Edukasi Lingua Sastra, 2023)
The kutub al-turats is the source of knowledge for Muslims after the Holy Qur'an and Hadith. Practically and theoretically, the ability to read the yellow book has degenerated. This requires follow-up to overcome practical and theoretical problems in the kutub al-turats. This study discusses the implementation of learning the mutammimah book on the ability to read the kutub al-turats at Madrasah Riyadlotusy Syubban Ponorogo. This study used a qualitative method, by describing the Mutammimah book learning method and its implications for the ability to read the yellow book. Sources of data were obtained by direct observation, as well as interviews with 1 Madrasah head, 4 Ustad and 7 students. Data analysis used content analysis which included data reduction, data display and conclusion. The results of the study show that learning the mutammimah book is capable of being a solution to practical and theoretical problems in the ability to read the kutub al-turats in Madrasah Riyadlotusy Syubban.